Evaluation of estates as an information source for the protection of the cultural heritage - Oktem, Nisa (Qualitative and Quantitative Methods in Libraries; Vol 6 No 3 (2017): September 2017 Issue, 2019)
Estates are one of the primary sources used as historical data in terms of revealing the socio-economic and cultural photograph of a region. These sources are document types which are either issued in the form of records as detached, or commonly used in Kadı Registers. Estates which is the name given to those who were left behind by a deceased person are very important information sources in the field of Ottoman economic and social history studies, because in these sources, there are crucial clues about economic and social life of the deceased person. On the other hand, estate records can be evaluate as a type of cultural heritage to shed light on Ottoman cultural life for researchers. As a result, this study will focus on how to use the estate records which are considered as the primary sources as an information source and the usage areas in Turkey.